2020
DOI: 10.1101/2020.08.19.257469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Nanoluciferase biosensor to investigate endogenous chemokine secretion and receptor binding

Abstract: Secreted chemokines are critical mediators of cellular communication that elicit intracellular signalling by binding membrane-bound receptors. Here we demonstrate the development and use of a sensitive real-time approach to quantify secretion and receptor binding of native chemokines in live cells to better understand their molecular interactions and function. CRISPR/Cas9 genome-editing was used to tag the chemokine CXCL12 with the Nanoluciferase fragment HiBiT. CXCL12 secretion was subsequently monitored and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In our initial experiments we also noted that CXCL17 inhibits basal/constitutive CXCR4 signalling, suggesting inverse agonist activity. However, CXCL12 is endogenously expressed in HEK293 cells at levels sufficient to initiate signalling 29 . To investigate if CXCL17 was disrupting signalling mediated by endogenous CXCL12, we took advantage of HEK293 cells engineered using CRISPR/Cas9 genomeediting to express CXCL12 tagged with a small 11 amino acid self-complementing fragment of NLuc (HiBiT).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our initial experiments we also noted that CXCL17 inhibits basal/constitutive CXCR4 signalling, suggesting inverse agonist activity. However, CXCL12 is endogenously expressed in HEK293 cells at levels sufficient to initiate signalling 29 . To investigate if CXCL17 was disrupting signalling mediated by endogenous CXCL12, we took advantage of HEK293 cells engineered using CRISPR/Cas9 genomeediting to express CXCL12 tagged with a small 11 amino acid self-complementing fragment of NLuc (HiBiT).…”
Section: Resultsmentioning
confidence: 99%
“…Nluc was then sub-cloned into the vector from existing constructs using the restriction enzymes XhoI and ApaI. Generation of pcDNA3.1 (+) neo expression constructs encoding NLuc/CXCR4, HiBiT/CXCR4 49 , SNAP/CXCR4 29 , NLuc/VEGFR2 36 and NLuc/NRP 35 have been described previously, as have pcDNA3 expression constructs encoding CXCR4/Rluc8 50 , CXCR4/N luc 51 , β-arrestin2/Venus 52 . Venus/G γ2 was a kind gift from Dr. Martina Kocan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technology has been employed with success in a number of studies designed to understand the biology of GPCRs [25] as well as a study on the co-receptor for Wnt/β-catenin signalling, LRP6 [26]. Among these, several studies have reported on NanoBRET ligand binding to endogenous class A GPCRs, mostly in HEK293 cells [27][28][29][30][31][32]. Here, as a continuation of our studies on ligand binding in the class F GPCRs [13,14,33], we measured the binding of the only available functional fluorescent WNT -eGFP-tagged mouse WNT-3A [14,34] -to endogenous FZD7 in SW480 cells typifying colorectal cancer, aiming to apply a more relevant cell model.…”
Section: Introductionmentioning
confidence: 99%